2017
DOI: 10.1002/hyp.11239
|View full text |Cite
|
Sign up to set email alerts
|

A framework to assess the cumulative impacts of dams on hydrological regime: A case study of the Yangtze River

Abstract: Comparisons of flow time series between preimpact and postimpact periods have been widely used to determine hydrological alterations caused by reservoir operation. However, preimpact and postimpact periods might also be characterized by different climatological properties, a problem that has not been well addressed. In this study, we propose a framework to assess the cumulative impact of dams on hydrological regime over time. The impacts of the Three Gorges Dam (TGD) on the flow regime of the Yangtze River wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 50 publications
2
39
0
Order By: Relevance
“…The Yangtze River is one of the longest rivers around the world, which collects water from several catchments [43]. The flow is monitored through several gauges along the river [44]. The Yangtze River covers one-fifth of the entire country with a region of about 1.8 million km 2 .…”
Section: Case Study and Datasetsmentioning
confidence: 99%
“…The Yangtze River is one of the longest rivers around the world, which collects water from several catchments [43]. The flow is monitored through several gauges along the river [44]. The Yangtze River covers one-fifth of the entire country with a region of about 1.8 million km 2 .…”
Section: Case Study and Datasetsmentioning
confidence: 99%
“…The changes of the downstream flow process appear to be the most direct and apparent results of the regulation of the TGD and have been widely studied. It has been revealed that the TGD displayed multiple behaviours altering downstream flow characteristics, such as decreasing and increasing discharge during the impoundment and release periods, respectively, and attenuating extreme flood peaks (Dai, Du, Li, Li, & Chen, 2008;Gao et al, 2012;Lai et al, 2014Lai et al, , 2017Mei et al, 2018;Wang, Wang, Lewis, Wu, & Huang, 2017). These variations in flow process due to the TGD were found to induce further hydrological alterations in water levels, droughts, interrelationships between the river and lakes, and even ecosystems of the downstream region (Guo et al, 2012;Li, Xiong, Dong, & Zhang, 2013;Mei, Dai, van Gelder, & Gao, 2015;Wang et al, 2013;Wang, Rhoads, & Wang, 2016;Wang, Sheng, & Wada, 2017;Zhang et al, 2012;Zhang, Ye, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The eco-flow metrics have been successfully applied for analyzing flow regime changes in different regions [20][21][22]. Gao et al [23] and Wang et al [24] found that the eco-flow metrics can describe changes in the hydrological parameters of groups 1 and 2 of the IHA metrics (i.e., the magnitude of monthly runoff and the magnitude of extreme runoff, respectively). This finding provides an opportunity to reduce the number of metric parameters used for the evaluation of flow regime changes using the eco-flow metrics.…”
Section: Introductionmentioning
confidence: 99%